Transient stability based dynamic security assessment indices. Issue 1 (1st January 2017) - Oyekanmi, Waheed Ayinla; Radman, Ghadir; Ajewole, Titus Oluwasuji
Abstract: As power systems become increasingly stability constrained, the need for dynamic security assessment (DSA) becomes important. However, the resources and technology required to achieve on-line DSA at reasonable cost for utility companies are not easily come by. Therefore, an offline method is needed to examine and screen all likely contingencies to determine those that may lead to instability. Some indices and techniques have been proposed to tackle this problem but are mostly for small disturbances which are not really threats when timely cleared. Some methods are based on evolutionary computation which comes with a lot of drawbacks as there is no guarantee of finding optimal solutions within a finite time and parameter tuning are mostly by trial-and-error. In this paper, a simpler approach to power system DSA indices is proposed using time domain transient stability analysis simulations. A conventional power system which synchronous machines are modeled with two-axis dynamic model, and modeled by Differential and Algebraic Equations, is used and solved numerically taken advantage of MATLAB ODE solver. The proposed indices are tested by carrying out N − 1 contingency on the transmission network of an IEEE 57-Bus test system to determine contingency cases that are likely to lead to system instability. The indices are validated by comparing their results with those obtained through an established DSA index called Angle Index in literature. Finally, effects of synchronous machine models on the indices are tested by comparing the results of the proposed functions with those obtained through synchronous machine classical model.